PENGARUH MODEL PEMBELAJARAN PROJECT-BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MARKETING KELAS XI BISNIS DIGITAL SMK NEGERI 6 MEDAN T.A 2024/2025 - Mei Hotma Purba; Novita Indah Hasibuan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of the Project-Based Learning (PjBL) model on student learning outcomes in the Marketing subject of Grade XI Digital Business students at SMK Negeri 6 Medan for the 2024/2025 academic year. This research employed an experimental method with a pretest-posttest control group design. The sample consisted of 67 students divided into two classes: the experimental class using the PjBL model and the control class using conventional learning. Data collection techniques included observation, documentation, and tests. The results showed a significant improvement in learning outcomes in the experimental class compared to the control class. The average post-test score of the experimental class was 85.00, while the control class scored only 70.45. The independent sample t-test showed a Sig. (2-tailed) value of 0.000 < 0.05 and a t-value of 5.648 > t-table value of 1.997, indicating a positive and significant effect of the PjBL model on student learning outcomes. Thus, the PjBL model is effective in improving student performance in the Marketing subject.